Inequality in the quality of women’s work and challenges in management (Journal of Universal Excellence, 2026)
Research Question (RQ): What led to the fact that fewer women occupy higher paid job positions and why gender differences still occur? We are investigating the problem of wage inequality between men and women and the employment options for women in the business world.Purpose: The purpose of the research was to determine the current state of education and further education, employment, gross wages and wage supplements, and the attitude of the owner or manager towards women working in management and leading positions.Method: In the study we used a qualitative approach. We arranged four individual interviews, thereby obtaining answers about education, wages, employment and workplace relations. The questions were prepared beforehand, and all interviewed persons were asked the same questions and were given the same instructions, so the interviews were semi-structured. Our sample is not random and is consequently subjective, since we interviewed women from defined age groups.Results: We have found that women’s job positions today differ significantly from their employments in the past. Women now have better opportunities for education and promotion at workplace, and at the same time the pay gap between men and women is slowly disappearing.Organization: The results of the survey offer information to owners and managers of specific companies and other institutions on how to work towards gross wages and wage supplements and how to act with regard to their relations towards employees.Society: The findings of the theoretical and empirical part of the research about the perception of inequality will influence the sustainable development of society from two aspects, economic and social.Originality: In the theoretical part of the research, we presented research and practical findings about the perception of inequality, with an emphasis on the management of organizations. We obtained original information on gross wages and wage supplements and on the relationship of company owner or manager towards women.Limitations/Future Research: A qualitative research on the perception of inequality from the perspective of women has methodological and substantive limitations. We presented suggestions for further research in the field of inequality in companies and other organizations, with an emphasis on their management and representation in top management.
Keywords: inequality; interview; job; management; organization; women’s work